Inventarisasi Kejadian Penyakit pada Ternak Kambing Bantuan Pemerintah di Desa Petaling Jaya, Kecamatan Kumpeh Ulu, Kabupaten Muaro Jambi Propinsi Jambi - Rahayu, Pudji (Fakultas Peternakan Universitas Jambi, 2008)
The survey research was conducted to investigate disease grouping which spred among governmental grat goat in desa Petaling Jaya. Thirty six farmers which owned 304 heads were used as respondent. Data collected were disease groups according to spreading into goat and diseases which were found during research time. The result indicated that al of the farmers (100%) reported that their goat had spred by scabies, 100 % worm, milk production problem (100%), 16 respondents (44.4%) feed consuption problem and 5 respondents (14%) swollen disease. However, there were only 4 kinds of diseases which caused goat death such as scabies, milk production problem, feed consumption problem and swollen disease. From the result we concluded that there were 4 kinds of diseases which were spred into goat in that region such as scabies, worm, milk production problem and feed consumption problem.